OPPORTUNITIES AND BARRIERS FOR LOCAL ENTREPRENEURS TO PARTICIPATE IN PUBLIC FOOD PROCUREMENT IN REZEKNE MUNICIPALITY - Zvaigzne, Anda; Znotiņa, Daina; Kotāne, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In recent years both in the world and in Latvia, food consumption as close to the production site as possible or local food has been increasingly discussed among scientists and the general public. According to a number of authors, the demand for local products increases, and localness is one the most latest trends in the global food market. Local food systems, in which the production, processing, sale and consumption of food products occurs within relatively small distances, make a significant positive effect on the local economy.The paper is based on the implementation results for the research grant "Opportunities for the Green Public Procurement of Food by Municipal Institutions in Rezekne Municipality”. The research aim is to identify the opinions of local entrepreneurs on their opportunities for and barriers to participating in public food procurement in Rezekne municipality.Research methods used: monographic, descriptive, analysis, synthesis, statistical (data grouping, cross-table analysis, averages) and a sociological research method – a pilot survey of local food production, processing and sale enterprises. The pilot survey of entrepreneurs showed that the enterprises which rated their readiness to participate in municipal public procurement tenders as very low and low justified this fact by their inability to supply the required quantity and assortment of products throughout the whole period specified, the lack of knowledge of green public procurement and the short period for paperwork, which could be classified as the lack of motivation for their participation in GPP.The survey questionnaires included a question aiming to identify the enterprises’ ratings of the key barriers to participating in public food procurement. The respondents rated the following barriers at five or as very significant: too low purchase prices on products, an insufficiently broad assortment of the products, an inability to supply the necessary quantity of the products, an inability to ensure regular deliveries of the products and a too long distance to deliver the products.